Differentiation and Characterization of Myeloid Cells. (4th February 2014) - Gupta, Dipti; Shah, Hetavi Parag; Malu, Krishnakumar; Berliner, Nancy; Gaines, Peter
Abstract: Ex vivo differentiation of myeloid cells begins with an enriched population of bone marrow–derived hematopoietic stem cells generated by lineage depletion and/or positive selection for CD34 + antigen (human) or Sca‐1 + (mouse) cells, which are then expanded and subsequently induced in vitro in a process that recapitulates normal myeloid development. Myeloid cell lines include two human leukemic cell lines, NB‐4 and HL‐60, which have been demonstrated to undergo retinoic acid–induced myeloid development; however, both cell lines exhibit defects in the up‐regulation of late‐expressed neutrophil‐specific genes. Multiple murine factor–dependent cell models of myelopoiesis are also available that express the full range of neutrophil maturation markers, including: 32Dcl3 cells, which undergo G‐CSF‐induced myeloid maturation; EML/EPRO cells, which develop into mature neutrophils in response to cytokines and retinoic acid; and ER‐Hoxb8 cells, which undergo myeloid maturation upon removal of estradiol in the maintenance medium. In this unit, the induction of myeloid maturation in each of these model systems is described, including their differentiation to either neutrophils or macrophages, if applicable. Commonly used techniques to test for myeloid characteristics of developing cells are also described, including flow cytometry and real time RT‐PCR. Curr. Protoc. Immunol . 104:22F.5.1‐22F.5.28. © 2014 by John Wiley & Sons, Inc.